Performance characteristics of top-level youth judokas in light- and heavy-weight categories - Engwerda, I. M.; Lidor, R.; Elferink-Gemser, M. T. (International Journal of Sports Science & Coaching, 2020)
Professionals involved in training programs for judokas should have access to evidence-based data on various characteristics of these athletes. In the current study, anthropometric (e.g., body height, body mass), physiological (e.g., power based on vertical jump height, maximal handgrip strength), and psychological (e.g., athletic coping skills) characteristics of judokas were examined. The judokas, aged 16-21, were classified into two groups: 30 light weight (males = 19, females = 11) and 27 heavy weight (males = 13, females = 14). Four MANCOVAs separated by sex were performed on the anthropometric, physiological, and psychological data. A discriminant analysis was also carried out. Results showed that heavy-weight males outscored their lighter peers on body height (d = 1.88), arm span (d = 1.88), and maximal handgrip strength. In the females, light-weight judokas outscored their heavier peers on jumping ability (d = 1.02) and peak power bench press (d = 1.20). Female heavy-weight judokas had greater body height (d = 1.46), a longer arm span (d = 1.35), and higher scores on maximal handgrip strength than light-weight judokas. The discriminant analysis revealed that 87.5% and 84.0% of the original grouped male and female judokas, respectively, were correctly classified. No differences in coping skills or self-regulation of learning between categories were observed. It is recommended that professionals involved in training programs may consider these differences in data when developing training programs for young judokas.